Kosmologi Ikhwan al-Shafa’ - Muhammad Abdullah Darraz (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2014)
This article is an attempt to examine and restructurize Ikhwan al-Shafa’s cosmological views. People’s perception of nature developing in the 10th century was that the nature was viewed in a more holistic approach. Nature is perceived as spiritualmetaphysic and material entity. This kind of approach is relevant to the current context after for centuries modern science, especially modern cosmological concept, has neglected spiritual-metaphysical dimension of the nature, and has only recognized the physical-material dimension of the nature. Therefore, over centuries teh meaning of nature has been reduced and this has led to inappropriate treatment toward nature. The author argues that the current perception of nature which neglects spiritual dimension has led to global environment crisis. Therefore, the holistic Ikhwan al-Shafa’s cosmological perspective is worth and relevant to current needs of humankind. Kata Kunci: Ikhwan al-Shafa’, cosmology, spiritual structure, material structure, universal active intellect.